Strategi Komunikasi Pemasaran Usaha Mikro Kecil dan Menengah (UMKM) Marjan dalam Meningkatkan Pendapatan Penjualan Kain Tenun Bima di Kelurahan Ntobo (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This research aims to explore the marketing communication strategies applied by Marjan MSMEs in increasing the sales income of Bima woven fabrics in Ntobo Village. The type of research conducted is qualitative descriptive research using the theory of Integrated Marketing Communication (IMC). The place where this research was carried out was at MSMEs Marjan Rt 01, Rw 01, Ntobo Village, Raba District, Bima City. The study involved four informants, consisting of two key informants who are owners or managers of Marjan MSMEs, and two additional informants who are consumers or customers of Bima woven fabrics from Marjan MSMEs. The data collection techniques used include observation, interviews, and documentation. The results of this study are expected to provide a comprehensive overview of effective marketing communication strategies in increasing sales revenue of Bima woven fabrics, as well as provide recommendations that can help Marjan MSMEs in improving their marketing performance. As well as showing that Marjan MSMEs can increase sales of their products by planning marketing strategies through social media and direct media. The supporting factors in the marketing of Marjan MSMEs are the affordable price of products because they are direct producers, as well as the relatively small capital spent because they utilize social media and direct promotion. This conclusion provides an idea that an effective marketing communication strategy can be the key to improving MSME sales performance, by utilizing the potential of social media and direct promotion as the main means of reaching the market and increasing revenue.